An introduction to feminism - Finlayson, Lorna (Cambridge introductions to philosophy., 2016)
"As well as providing a clear and critical introduction to the theory, this refreshing overview focuses on the practice of feminism with coverage of actions and activism, bringing the subject to life for newcomers as well as offering fresh perspectives for advanced students. Explanations of the main strands to feminism, such as liberalism, sit alongside an exploration of a range of approaches, such as radical, anarchist and Marxist feminism, and provide much-needed context against which more familiar historical themes may be understood. The author's borad and inclusive view conveys the diversity and disagreement within feminism with accessible clarity. The analysis of key terms equips readers with a critical understanding of the vocabulary of feminist debates that will be invaluable to undergraduate students."